An Integrated Approach to Improve Maternal Mental Health and Well-Being During the COVID-19 Crisis - Shidhaye, Rahul; Madhivanan, Purnima; Shidhaye, Pallavi; Krupp, Karl (Frontiers in Psychiatry, 2020)
The ongoing COVID-19 pandemic has led to disruption of normal life across the globe, severely affecting the already vulnerable populations such as the pregnant women. Maternal mental health and well-being is a public health priority and the evidence about the impact of COVID-19 on mental health status of pregnant women is gradually emerging. The findings of the recently published studies suggest that increased risk perception about contracting COVID-19, reduced social support, increase in domestic violence, disruption of antenatal care, and economic consequences of COVID-19 mitigation strategies can lead to adverse mental health outcomes in antenatal period. There is a significant increase in antenatal depression and anxiety since the onset of COVID-19 and social determinants of health (e.g. younger age, lower education, lower income) are associated with these poor outcomes. In this paper, we propose an integrated approach to improve the mental health and well-being of pregnant women. Physical activity and/or mind-body interventions like yoga can be practiced as self-care interventions by pregnant women. Despite social distancing being the current norm, efforts should be made to strengthen social support. Evidence-based interventions for perinatal depression should be integrated within the health system and stepped, collaborative care using non-specialist health workers as key human resource be utilized to improve access to mental health services. Use of digital platforms and smartphone enabled delivery of services has huge potential to further improve the access to care. Most importantly, the COVID-19 related policy guidelines should categorically include maternal mental health and well-being as a priority area.